Haematological changes in active chronic hepatitis with reference to the role of the spleen. - Toghill, P J (1975)
The haematological role of the spleen has been investigated in a series of 22 patients with active chronic hepatitis. Severe pancytopenia occurred in one patient after three years of steroid therapy and this episode was associated with an increase in spleen size and a high splenic index of red cell destruction. Although the spleen was usually enlarged in the remainder of treated and untreated patients no others showed increased splenic haemolysis. The red cell survival was slightly reduced in most patients but splenic pooling of red cells and expansion of the plasma volume did not significantly reduce the haematocrit level. No consistent haematological differences were detected between the untreated and the treated patients.